The traditional Malay architectural world view (with emphasis on the role of the tukang) - Abdul Rahman, Abdul Razak (Universiti Teknologi Malaysia, 1999)
This paper seeks to explain the traditional Malay Architecture world view by reviewing the concepts of traditional Architecture and the Malay world view through communal practice, beliefs and ethics of the society as well as individual craftsmen. It is apparent that, contemporary architecture' lacks theoretical base, and therefore has no regional identity